Outer Membrane Vesicles Protect Gram-Negative Bacteria against Host Defense Peptides - Balhuizen, Melanie D; van Dijk, Albert; Jansen, Jeroen W A; van de Lest, Chris H A; Veldhuizen, Edwin J A; Haagsman, Henk P (American Society for Microbiology, 2021)
Host defense peptides (HDPs) are part of the innate immune system and constitute a first line of defense against invading pathogens. They possess antimicrobial activity against a broad spectrum of pathogens. However, pathogens have been known to adapt to hostile environments. Therefore, the bacterial response to treatment with HDPs was investigated. Previous observations suggested that sublethal concentrations of HDPs increase the release of outer membrane vesicles (OMVs)in Escherichia coli. First, the effects of sublethal treatment with HDPs CATH-2, PMAP-36, and LL-37 on OMV release of several Gram-negative bacteria were analyzed. Treatment with PMAP-36 and CATH-2 induced release of OMVs, but treatment with LL-37 did not. The OMVs were further characterized with respect to morphological properties. The HDP-induced OMVs often had disc-like shapes. The beneficial effect of bacterial OMV release was studied by determining the susceptibility of E. coli toward HDPs in the presence of OMVs. The minimal bactericidal concentration was increased in the presence of OMVs. It is concluded that OMV release is a means of bacteria to dispose of HDP-affected membrane. Furthermore, OMVs act as a decoy for HDPs and thereby protect the bacterium
Keywords: Gram-negative bacteria; antibiotic resistance; antimicrobial peptides; host defense peptides; outer membrane vesicles; Microbiology; Molecular Biology